Analysis of Strategic Management in Small and Medium Business Organizations in Graphic Industry - Boshevska, Lili; Jolevski, Ilija (Journal of Graphic Engineering and Design, 2023)
Graphic industry as a field of work and a field of study offers ability for economic growth of every country or region. The increase in competition and the development of the market method of prediction, increase the need for business organizations to continuously observe their own position. Faced with a variable, turbulent and complex environment, the business organizations adopt strategic management, and modern managers, especially those in top management, have to possess knowledge and skills of the concepts and application of strategic management. In this paper the case method, as a method used in strategic management, will be applied as a general approach of strategic analysis in creating strategy map for businesses in graphic industry.